Focus groups : from structured interviews to collective conversations - Kamberelis, George; Dimitriadis, Greg, 1969- (Abingdon, Oxon ; New York, NY : Routledge, 2013)
'Focus Groups: From Structured Interviews to Collective Conversations is a conceptual and practical introduction to focus group. As the title indicates, focus groups traditionally encompass a wide range of discursive practices. These span from formal structured interviews with particular people assembled around clearly delimited topics to less formal, open-ended conversations with large and small groups that can unfold in myriad and unpredictable ways. Additionally, focus groups can and have served many overlapping purposes--from the pedagogical, to the political, to the traditionally empirical. In this book, focus groups are systematically explored; not as an extension or elaboration of interview work alone, but as its own specific research method with its own particular affordances. This book comprehensively explores: The nature of focus groups ; Politic and activist uses of focus groups ; Practical ways to run a successful focus group ; Effective analysis of focus group data ; Contemporary threats to focus groups. Focus Groups: From Structured Interviews to Collective Conversations is essential reading for qualitative researchers at every level, particularly those involved in education, nursing, social work, anthropology, and sociology disciplines.'--Publisher's website.
Focus groups: a brief and incomplete history -- Multiple, interrelated functions of focus group work -- Key affordances of focus group research -- Fundamental elements of effective focus group research practice -- Contemporary dilemmas and horizons of focus group research -- Epilogue.
Includes bibliographical references (p. [105]-109) and index.
Keywords: Focus Groups; Focus groups; Sozialwissenschaften; Methodologie; Gruppeninterview